Legal Protection for Teachers from the Threat of Criminalization in Instilling Student Discipline - Budoyo, Sapto; Widodo, Wahyu; Suyadi, Suyadi (Pandecta Research Law Journal, 2024)
Teachers as professional educators play a crucial role in efforts to educate the life of the Indonesian nation. Increasing the level of criminalization of teachers, due to the act of reporting teachers to the Police in certain cases when teachers are carrying out duties. This study aims to determine and analyze legal protection for teachers in instilling student discipline values from the threat of criminalization and analyze efforts to optimize teacher legal protection from the threat of criminalization in instilling student discipline. The urgency of this study is to see from the perspective of the case of teachers who are suspected of committing criminal acts, teachers as educators in carrying out professional duties are suspected of violating the law or suspected of committing criminal acts, where teachers in that case are carrying out their profession and in this study it is important to do because it is to provide understanding, especially teachers in carrying out their profession when faced with a legal problem. The research used data collection methods, namely mixed methods. Qualitative includes an interview guide for resource persons containing a list of questions or topics to be discussed in the interview. Quantitative is collecting and analyzing data based on numbers and numerical measurements. This approach aims to describe, explain, and test relationships between variables using statistical analysis. The results showed that teachers in carrying out their professional duties have not received maximum legal protection. The final results show that given the large number of cases involving teachers having to deal with the law, this needs to be handled seriously in protecting teachers' laws from the threat of criminalization in carrying out their professional duties and instilling discipline in students.